Internal friction and microstructure of ti and ti-mo alloys containing oxygen - Martins, J. R.S. [UNESP]; Araújo, R. O. [UNESP]; Nogueira, R. A. [UNESP]; Grandini, C. R. [UNESP] (De Gruyter, 2016)
Ti-Mo alloys are promising materials for use as biomaterials, because these alloys have excellent corrosion resistance and a good combination of mechanical properties such as fatigue, low elastic modulus, hardness, and wear resistance. The objective of this paper was to study the effect of heavy interstitial atoms on anelastic properties of Ti-Mo alloys using mechanical spectroscopy. The internal friction and Young's modulus were measured as a function of temperature using dynamic mechanical analyser. The internal friction spectra were brought about by relaxation processes attributed to shortrange stress induced reorientation of interstitial and substitutional complexes in solid solution. It is suggested that the ature of the relaxing entities can be worked out in further research on Ti-Mo single crystals.
Keywords: Anelasticity; Biomaterials; Internal friction; Interstitials; Mechanical spectroscopy; Ti-Mo alloys